IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH ELECTRONIC DICTIONARY - Sri Yanti (Indonesian EFL Journal, 2016)
This research is designed to investigate the use of electronic dictionary in improving students’ vocabulary mastery. This quantitative research applied quasi-experimental with nonequivalent control group design by involving 65 second-grader of SMAN 1 Garawangi. There were two instruments used in this research, namely test, consisted of pretest and posttest, and questionnaire. As result, the findings showed that the mean score of experimental class on pretest was 53, and the mean score of experimental class achieved 86 after the treatment. The improvement of students’ vocabulary mastery can also be seen from the level of significance (two-tailed) in paired t-test that was less than the alpha (0.0000.05). It indicated that the null hypothesis was rejected and Ha was accepted which means that there was significant difference of means between pre-test and post-test of experimental class. Besides, most students endorsed ten items of questionnaire involving affective, behavioral, and cognitive aspects which means that most students in experimental class agreed that electronic dictionary can help them in improving their vocabulary mastery. Finally, the researcher concludes that the use of electronic dictionary can improve students’ vocabulary mastery.Keywords: electronic dictionary, vocabulary mastery, quasi-experimental, nonequivalent control group